2020
DOI: 10.3390/app10238428
|View full text |Cite
|
Sign up to set email alerts
|

SiO2/C Composite as a High Capacity Anode Material of LiNi0.8Co0.15Al0.05O2 Battery Derived from Coal Combustion Fly Ash

Abstract: Abundantly available SiO2 (silica) has great potential as an anode material for lithium-ion batteries because it is inexpensive and flexible. However, silicon oxide-based anode material preparation usually requires many complex steps. In this article, we report a facile method for preparing a SiO2/C composite derived from coal combustion fly ash as an anode material for Li-ion batteries. SiO2 was obtained by caustic extraction and HCl precipitation. Then, the SiO2/C composite was successfully obtained by mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…Jumari et al 22 reported a similar result, where the increase in SiO 2 content in SiO 2 /C resulted in a high specific capacity. However, the initial CE tended to decrease.…”
Section: Sio 2 Content In Composite Sio 2 /Cmentioning
confidence: 70%
See 4 more Smart Citations
“…Jumari et al 22 reported a similar result, where the increase in SiO 2 content in SiO 2 /C resulted in a high specific capacity. However, the initial CE tended to decrease.…”
Section: Sio 2 Content In Composite Sio 2 /Cmentioning
confidence: 70%
“…Recently, waste or industrial side products have been widely used as a source of SiO 2 . For example, Jumari et al 22 synthesized SiO 2 /C using fly ash combustion as a source of SiO 2 , Wu et al 50 used electronic waste, and Widiyandari et al 23 used geothermal sludge for the synthesis of SiO 2 /Mg. The use of waste or industrial side products potentially reduces the production cost of lithiumion batteries and can overcome environmental problems.…”
Section: Sources Of Silica For Sio 2 /C Anodementioning
confidence: 99%
See 3 more Smart Citations